(untitled) (Ameghiniana, 2014)
The section considered is the upper part of the Vaca Muerta Fm. sensu Leanza (1973). It has yielded the first marine microfloras of Berriasian age from Argentina (12 species of dinocysts and 4 of acritarchs). The genera present are cf. Rhaetogonyaulax, Pareodinia, Gonyaulacysta, Cribroperidin ium ,Millioudodin ium, A cantaulax, Ctenidodinium, Hystrichosphaerina, Sy stematophora, Proli:xosphaeridium, Sentusidinium, Lithodinia, Micrhystridium, Cymatiosphaera and Leiosphaeridia. Amongst the terrestrial genera, Alisporites, Anapiculatisporites, Araucariacites, Callialasporites, Converrucosisporites,. Classopollis, Cycadopites, C;Tclogranisporites, Deltoidospora, Equisetosporites, Eucommiidites, Inaperturopollenites, Leptolepidites, Lycopodiumsporites, Microcachryidites, Monosulcites, Phrixipollenites, Pilasporites, Podocarpidites, Stereisporites, Trisaccites, Verrucosisporites and Vitreisporites have been observed. The microfloras are compared with other Jurassic and Lower Cretaceous palynomorph assemblages from the same basin and other regions. From statistical study there microfloristic assemblages some environmental data are inferred.